EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII DI SMP AL-RAHMAH JAKARTA - Novita Diyanti, Siti Azizah; Akil, Akil; Nurlaeli, Acep (Universitas Islam Negeri Sumatera Utara Medan, 2023)
This research is motivated by the low learning outcomes of students in PAI subjects. The solution is to apply the Problem Based Learning model. The purpose of this study was to determine the implementation and effectiveness of the PBL model to improve the learning outcomes of class VII PAI students at SMP Al Rahmah Jakarta. The research method used in this study is the Quasi Experiment method. The sample in this study were 32 students consisting of 16 students in the experimental class (VII B) and 16 students in the control class (VII A). In the learning process, the results of this study revealed an increase in student learning outcomes using the PBL learning model. Evidenced by the average value of the experimental class of 85.94 and the average control class of 78.44. In addition, through the N-Gain Independent Sample T-Test it was found that > 2.825 > 2.321) and Sig. (2-tailed) 0.027 <0.05, so that Ha is accepted and Ho is rejected. This shows that there is a significant effectiveness between the experimental class that uses PBL and the control class that does not use it.